2014
DOI: 10.1136/thoraxjnl-2014-206260.247
|View full text |Cite
|
Sign up to set email alerts
|

P106 Sputum Induction Reduces The Need For Bronchoscopy In School-aged Children With Cystic Fibrosis

Abstract: Introduction The lower airway microbiota is important in chronic lung disease but young children do not expectorate, making longitudinal studies difficult. Upper airway samples, of uncertain reliability, are used as a surrogate. Whilst throat swabs (TS) have shown differences in the microbiota between healthy and wheezing children [PLoS One 2012;7(10):e46803], the role of cough swabs (CS) is at present unclear. This study assessed the correlation between upper and lower airway samples as a prelude to a longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…27,28 However, this procedure is invasive, requires a general anaesthesia, is expensive and may itself cause inflammation. 29 Sputum induction using nebulized hypertonic saline is an alternative 30,31 to obtain lower airway samples with minimal discomfort to the patient. 32,33 Previous studies have shown that induced sputum samples correlate well with BAL samples with respect to bacterial load and pathogens isolated.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 However, this procedure is invasive, requires a general anaesthesia, is expensive and may itself cause inflammation. 29 Sputum induction using nebulized hypertonic saline is an alternative 30,31 to obtain lower airway samples with minimal discomfort to the patient. 32,33 Previous studies have shown that induced sputum samples correlate well with BAL samples with respect to bacterial load and pathogens isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF) microbiological surveillance ‐Routine microbial surveillance in CF, particularly in those who do not produce sputum 9 ‐Sputum induction reduces the need for bronchoscopy in school‐aged children with CF 10 but is not always sensitive for lower airway infection 11 . Sputum‐induction can potentially be performed at home in children older than 5 years, 12 provided previous tolerance to and safety of hypertonic saline has been determined in the child. ‐Induced sputum has been proposed as a sensitive method for use in preschool aged children 13 .…”
Section: Indications For Sputum Inductionmentioning
confidence: 99%